Konstruksi Akad Ijarah Multi Jasa di KSPPS Anugerah Cabang Seomerto Perspektif Fatwa DSN-MUI No: 44/DSN-MUI/VII/2004 - Kinanti, Sara (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
One of MUI's efforts to maintain Islamic law in LKS products is to issue DSN-MUI Fatwas which regulate LKS products in Indonesia. The lack of knowledge and the nature of the fatwa that do not remember lead to many violations in the issued fatwas. For this reason, this study intends to find out that the Multi-service Ijarah Contract at the Selomerto branch of KSPPS Anugerah is in accordance with the DSN-MUI fatwa on multi-service financing or not. This study found: first, the implementation of Multiservice Financing at KSPPS Anugerah Selomerto branch using an ijarah contract where KSPPS acts as an ajir and members as Musta'jir with the object of the contract in the form of services provided by KSPPS in return for ujrah/fees given by members to KSPPS. Second, the Ijarah Mutijasa Agreement at KSPP Anugerah is not in accordance with the DSN-MUI Fatwa No. 44/DSN-MUI/VII/2004 concerning Multi-service financing which also refers to 2 other fatwas, namely DSN-MUI Fatwa No. 09/DSN-MUI/IV/2004 and no. 112/DSN-MUI/IX/2017 regarding Ijarah financing. The Multi-service Ijarah Financing Agreement at KSPPS Anugerah Selomerto branch does not fulfill the pillars of ijarah. In addition, the provisions of ujrah or fees are also contrary to the provisions in the fatwa.